Artikel Review : Pengaruh Penyalutan Terhadap Karakteristik Fisikokimia Tablet Salut Gula atau Enterik - Nisful Lailatun Nadiroh; Dwi Roisiyah; Salsabiila Wina Delia; Najwa Firida Rahma; Adela Gerlani Bria; Rusdiana Tri Septiarini; Jihan Fahiroh Nur Arifin; Dewi Rahmawati; Yani Ambari; Dzakiya Zhihrotul Wida (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Tablet coating is one of the pharmaceutical technologies that plays an important role in improving the physicochemical characteristics and stability of tablet preparations. This study aims to comprehensively review the effect of coating processes on the physicochemical characteristics and stability of tablets, including mechanical properties, dissolution profiles, and active substance stability during storage. The method used is a literature review of 8 scientific journals obtained from Google Scholar, PubMed, PerpusNas, and ResearchGate databases, published within the last 5–10 years. The results showed that the coating process significantly affected physicochemical characteristics including hardness, friability, disintegration time, dissolution profile, and drug release. In terms of stability, coating protected active substances from environmental influences such as humidity, oxidation, and gastric acid degradation. Among the types of coating studied, enteric coating proved to be the most effective method as it provided maximum protection for acid-sensitive drugs and specifically controlled drug release in the intestine, thereby positively impacting bioavailability and therapeutic efficacy. Sugar coating also contributed to improving physical properties and protecting tablets during storage and distribution. Therefore, selection of appropriate coating type and composition is a critical factor in producing quality, stable, and therapeutically effective tablet preparations.